Survey and Surveillance of Curculio c-album and Conogethes punctiferalis on Jamun (Syzygium cuminii) - Hirekurubar, R. B.; Tatagar, M. H.; Ramegowda, G. K.; Patil, Suvarna; Sabarad, A. I.; Naika, Mahantesha B.N.; Mastiholi, A. B. (International Journal of Bio-resource and Stress Management, 2023)
Fixed plot survey was carried out at fortnightly intervals from March to July, 2021 and 2022 jamun fruiting season at six locations of Belagavi district of Karnataka, India. Survey locations comprised in the study were fruit orchard of KRC College of Horticulture Arabhavi, Dupadal, Ankalagi, Kolavi, Kaitanal and Hidkal Dam with six available varieties viz., Dupadal, Kolavi local, Kaitanal local and Hidkal Dam local, Konkan Bahadoli and AJG-85. Pooled data of 2021 and 2022 for fruit damage due to fruit and seed weevil, Curculio c-album revealed that pest incidence starts with an onset of fruit formation and continues till harvesting of fruits. The overall mean fruit damage percentage ranged from 12.3–41.5% with peak incidence during second fortnight of June. Across all the locations highest (50.1%) fruit damage was noticed in Dupadal variety at Dupadal and at the same time less (19.0%) fruit infestation was observed in AJG-85 at Arabhavi. The overall mean of jamun fruit damage due to Conogethes punctiferalis ranged from 0–3.6% with peak incidence during II fortnight of June. Correlation analysis between percentage fruit infestation due to Curculio c-album and Conogethes punctiferalis with prevailing major weather parameters were studied in cv. Konkan Bahadoli. The fruit infestation due to C. c-album and Conogethes punctiferalis was negatively correlated with temperature, positively correlated with relative humidity. C. c-album had positive correlation with rainfall whereas C. Punctiferalis was negatively correlated with rainfall.